Response of ionospheric electric fields to variations in the interplanetary magnetic field - Mishra S.P.; Nielsen E. (My University, 2025)
The STARE system (Scandinavian Twin Auroral Radar Experiment) provides estimates of electron drift velocities, and hence also of the electric field in the high-latitude E-region ionosphere between 65 and 70 degrees latitude. The occurrence of drift velocities larger than about 400 m/s (equivalent to an electric field of 20 mV/m) have been correlated with the magnitude of the Interplanetary Magnetic Field (IMF) components Bz and By at all local times. Observation days have been considered during which both southward (Bz < 0) and northward (Bz > 0) IMF occurred. The occurrence of electric fields larger than 20 mV/m increases with increases in Bz magnitudes when Bz < 0. It is found that the effects of southward IMF continue for some time following the northward turnings of the IMF. In order to eliminate such residual effects for Bz < 0, we have, in the second part of the study, considered those days which were characterized by a pure northward IMF. The occurrence is considerably lower during times when Bz > 0, than during those when Bz is negative. These results are related to the expansion and contraction of the auroral oval. The different percentage occurrences of large electric field for By > 0 and By < 0 components of the IMF during times when Bz > 0, clearly display a dawn-dusk asymmetry of plasma flow in the ionosphere. The effects of the time-varying solar-wind speed, density, IMF fluctuations, and magnetospheric substorms on the occurrence of auroral-backscatter observations are also discussed.